Methyl sulfates as methoxy isotopic reference materials for [delta]13C and [delta]2H measurements - Greule, Markus; Keppler, Frank (Rapid communications in mass spectrometry, 2019)
Rationale Stable hydrogen and carbon isotope ratios of methoxy groups (OCH3) of plant organic matter have many potential applications in biogeochemical, atmospheric and food research. So far, most of the analyses of plant methoxy groups by isotope ratio mass spectrometry have employed liquid iodomethane (CH3I) as the reference material to normalise stable isotope measurements of these moieties to isotope-δ scales. However, comparisons of measurements of stable hydrogen and carbon isotopes of plant methoxy groups are still hindered by the lack of suitable reference materials. Methods We have investigated two methyl sulfate salts (HUBG1 and HUBG2), which exclusively contain carbon and hydrogen from one methoxy group, for their suitability as methoxy reference materials. Firstly, the stable hydrogen and carbon isotope values of the bulk compounds were calibrated against international reference substances by high-temperature conversion- and elemental analyser isotope ratio mass spectrometry (HTC- and EA-IRMS). In a second step these values were compared with values obtained by measurements using gas chromatography/isotope ratio mass spectrometry (GC/IRMS) where prior to analysis the methoxy groups were converted into gaseous iodomethane. Results The 2H- and 13C isotopic abundances of HUBG1 measured by HTC- and EA-IRMS and expressed as δ-values on the usual international scales are −144.5 ± 1.2 mUr (n = 30) and −50.31 ± 0.16 mUr (n = 14), respectively. For HUBG2 we obtained −102.0 ± 1.3 mUr (n = 32) and +1.60 ± 0.12 mUr (n = 16). Furthermore, the values obtained by GC/IRMS were in good agreement with the HTC- and EA-IRMS values. Conclusions We suggest that both methyl sulfates are suitable reference materials for normalisation of isotope measurements of carbon of plant methoxy groups to isotope-δ scales and for inter-laboratory calibration. For stable hydrogen isotope measurements, we suggest that in addition to HUBG1 and HUBG2 additional reference materials are required to cover the full range of plant methoxy groups reported so far.
First published: 19 November 2018
Im Titel sind die Zahlen"13" und "2" hochgestellt
Im Titel ist delta als griechischer Buchstabe dargestellt
Gesehen am 15.02.2019